Interferon Regulatory Factor 4 dose-dependently controls peripheral Treg cell differentiation and homeostasis by modulating chromatin accessibility in mice - Leonie Caroline Voß; Constantin Schmidt; Constantin Schmidt; Aenne Harberts; Aenne Harberts; Aenne Harberts; Michael Spohn; Michael Spohn; Michael Spohn; Peter Bradtke; Alina Borchers; Alina Borchers; et al. (Frontiers in Immunology)
FoxP3+ regulatory T (Treg) cells restrict excessive immune responses and immunopathology as well as reactivity to self or environmental antigens and thus are crucial for peripheral immune tolerance. The transcription factor Interferon Regulatory Factor 4 (IRF4) controls differentiation and function of T cells. In Treg cells, IRF4 is required for peripheral activation and maturation to effector Treg (eTreg) cells with enhanced suppressive function. However, the mechanisms of Treg cell regulation by IRF4 are not fully understood. Here, we analyze the role of IRF4 in differentiation and maintenance of Treg cells using IRF4-deficient mice and a T cell transfer model, that allows Irf4 inactivation in peripheral T cells. We demonstrate that loss of one Irf4 allele already results in impaired eTreg cell differentiation and decreased Treg cell homeostasis, indicating that IRF4 controls peripheral Treg cell differentiation in a gene dosage dependent mode. Peripheral Irf4 inactivation was also associated with enhanced production of inflammatory but also inhibitory cytokines by Treg cells. ATAC sequencing of Treg cells after mutation of one or both Irf4 alleles revealed regions with altered accessibility in genes involved in Treg cell function. In the FoxP3 gene, Irf4 inactivation resulted in reduced ATAC signals in the promoter region and in the conserved non-coding sequence (CNS) 2, required for stability of FoxP3 expression in peripheral Treg cells in response to TCR stimulation. IRF4-deficient Treg cells also displayed a reduction in open chromatin in several Treg cell specific super enhancers, mainly located in proximity to potential IRF4 binding sites. In conclusion, our results demonstrate that IRF4 controls peripheral Treg cell differentiation and homeostasis in a gene dosage dependent manner.